A Viable Solution: The Case for Blended Delivery on an On-line Learning Programme - Miller, Christopher; Jones, Paul; Packham, Gary; Thomas, Brychan (Proceedings of the International Conference on Networked Learning, 2004)
The development of e-learning presents challenges for providers in terms of their need to re-engineer themselves to cater for the different demands of this educational frontier. This study profiles the BA Enterprise programme, designed by the University of Glamorgan and analyses the emergence of the blended pedagogical learning model that has evolved within this programme utilising a case study methodology. The course was conceived as an exclusively on-line programme but evolved into a hybrid-blended pedagogy. A framework for blended delivery is proposed alongside an identification of the key factors for the effective delivery of an on line course. This study contributes to knowledge by identification of the critical issues behind the development of a blended e-learning programme.